Essays in conveyancing and property law in honour of Professor Robert Rennie - MacCarthy, Frankie; Chalmers, James, 1976-; Bogle, Stephen; Rennie, Robert, 1947- (Open Book Publishers, 2015)
"Professor Robert Rennie has been one of the most influential voices in Scots private law over the past thirty years. Highly respected as both an academic and a practitioner, his contribution to the development of property law and practice has been substantial and unique. This volume celebrates his retirement from the Chair of Conveyancing at the University of Glasgow in 2014 with a selection of essays written by his peers and colleagues from the judiciary, academia and legal practice. Each chapter covers a topic of particular interest to Professor Rennie during his career, from the historical development of property law rules through to the latest developments in conveyancing practice and the evolution of the rules of professional negligence. Although primarily Scottish in focus, the contributions will have much of interest to lawyers in any jurisdiction struggling with similar practical problems, particularly those with similar legal roots including the Netherlands and South Africa. As a whole, the collection is highly recommended to students, practitioners and academics."--Publisher's website.